Price Discovery in Thinly Traded Futures Markets: How Thin is Too Thin? - Philipp Adaemmer; Martin T. Bohl; Groß Christian (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
We investigate the price dynamics of two illiquid agricultural futures contracts traded at the European Exchange in Frankfurt. Based on constant and time-varying vector error correction models, we measure the contribution of each futures market to price discovery. Although results from the constant model indicate a dominant role of both futures markets, time-varying parameters reveal strong fluctuations in the price discovery process of the less liquid futures market. By comparing the empirical results, we conclude that the trading volume threshold which is necessary to facilitate efficient price discovery is very low. Our findings also show that neglecting time-variation in the parameters can lead to misleading results, especially for thinly traded markets.
Keywords: G12; G13; Q11; 330